The significance of vertical gaze palsy in the paramedian thalamic artery syndrome - Weisbrod, Matthias; Kölmel, H. W.; Hättigand, H.; Lempert, Th (Neuro-ophthalmology, 2009)
The paramedian diencephalic syndrome is characterized by a clinical triad of hyper-somnolent apathy, memory loss, and abnormalities of vertical gaze. The authors introduce a patient with the typical syndrome of paramedian thalamic artery infarction. The extent of the infarction was studied by MR imaging. Bilateral infarcts of the medial thalamus-accounting for the behavioral syndrome-and lesions in the area of the rostral interstitial nucleus of the medial longitudinal fasciculus-accounting for the vertical gaze palsy-were identified.
Published online: 08 Jul 2009
Gesehen am 25.01.2021